Compound Words Reflect Cross‐Culturally Shared Bodily Metaphors. (14th August 2018) - Holmes, Kevin J.; Flusberg, Stephen J.; Thibodeau, Paul H.
Abstract: Parts of the body are often embedded in the structure of compound words, such as heartbreak and brainchild . We explored the relationships between the semantics of compounds and their constituent body parts, asking whether these relationships are largely arbitrary or instead reflect deeper metaphorical mappings shared across languages and cultures. In three studies, we found that U.S. English speakers associated the English translation equivalents of Chinese compounds with their constituent body parts at rates well above chance, even for compounds with highly abstract meanings and even when accounting for the semantic relatedness of the compounds and body parts. English speakers in India and Chinese speakers in Hong Kong showed similar intuitions about these associations. Our results suggest that the structure of compound words can provide insight into cross‐culturally shared ways of connecting meaning to the body.